Pengaruh Gaya Kepemimpinan Partisipatif Dan Kompensasi Terhadap Organizational Citizenship Behavior (OCB) Di PT. Urbane Indonesia - Hersili Wangi Shidikkusumah; Deden Sutisna (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the influence of participative leadership style and compensation on Organizational Citizenship Behavior (OCB) at PT. Urbane Indonesia. The research design uses a descriptive-verificative method with a quantitative approach. Data collection was carried out by distributing questionnaires to 52 employee respondents using a saturated sampling technique. The data analysis technique used is Multiple Linear Regression. Descriptive analysis shows that the employees' OCB level is excellent, with a mean score of 4.06. The results of the partial hypothesis test (t-test) show that both participative leadership style (t=8.440, p=0,000) and compensation (t=10.446, p=0,000) have a positive and significant effect on OCB. Simultaneously (F-test), both variables significantly influence OCB with an F-value of 85.74 (p=0.000). The coefficient of determination (R²) is 0.778, indicating that 77.8% of the variance in employee OCB is explained by participative leadership style and compensation, while the remaining 22.2% is influenced by other factors outside this research model. Compensation is identified as the most dominant factor in triggering extra-role behavior. quality of healthcare services.